Teenage girls waving from truck bed - Unknown:::Creator::::::::::::
Negative shows a large group of teenage girls posing from the bed of a truck parked outside the YWCA building. They are waving at the camera. A woman and one of the girls are standing in the front on the street. This is possibly a picture of members of the YWCA's Contenta Hora group. Contenta Hora was a YWCA club for Latinas.